PENERAPAN KEBIJAKAN MANAJEMEN KUALITAS DALAM MENINGKATKAN MUTU PENDIDIKAN ISLAM DI SEKOLAH - Putri Oktavia; Khusnul Khotimah; Ma'rup; Sairul Basri (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2023)
This study aims to examine the implementation of an effective evaluation and monitoring system in improving the quality of teaching Islamic education in schools. The research method used was qualitative research with a case study approach, involving the participation of Islamic education teachers from several schools as respondents. The results of the study show that the implementation of an effective evaluation and monitoring system has an important role in improving the quality of teaching Islamic education in schools. The research findings highlight the importance of setting indicators for achieving clear and measurable goals, which include aspects of religious knowledge, understanding of Islamic concepts, application in daily life, Islamic attitudes and values, and practical skills. In addition, the development of a comprehensive evaluation tool is a key factor in the implementation of this system. Written tests, oral tests, projects, class observations, and student portfolios are used as evaluation tools that cover various types of assessments. Technology utilization also plays an important role, with the use of software and applications that support the efficient collection, analysis and reporting of evaluation data. Furthermore, the involvement of teachers in the evaluation and monitoring process has proven to make a positive contribution. Teachers can provide valuable input and feedback to improve teaching methods, as well as identify areas that need improvement in the teaching of Islamic education. By implementing an effective evaluation and monitoring system, it is hoped that schools can continuously improve the quality of teaching Islamic education. This research contributes to an understanding of the importance of holistic and sustainable evaluation in supporting the development of quality Islamic education that is relevant to the times.